Women's Changing Participation in the Labor Force of Moroccan Economy. An Analysis of the Sensitivity on the Results of CGE Model - Mohamed Karim; Mohamed Bouzahzah (International Journal of Economics and Financial Issues, 2013)
Via an unconditional sensitivity analysis, we wish to check that the variability of the model as a whole is not too important in the event of simultaneous modification of all the parameters. To do this, the Gaussian quadrature method is implemented as developed by Arndt (1996), De Vuyst and Preckel (1997) and Piet (2002). From the methodological point of view, an unconditional sensitivity analysis allows to give evidence of the robustness of the results. A part from this analysis, we appreciate the reel effect, on the women’s participation in the labor market, of increasing commercial opening of the Moroccan economy. To do this, we build before a static multi-sector computable general equilibrium (CGE) model, which differentiates the work of men and women. The model is then calibrated on real data of the Moroccan economy before being used for analytical purposes. It highlights an improvement of the employment demand of womens in the main exporting sectors in particular the agriculture, food industry and that of the leather and textile industry.